2000
DOI: 10.1002/1097-0185(20000901)260:1<81::aid-ar90>3.0.co;2-3
|View full text |Cite
|
Sign up to set email alerts
|

Anatomy of the human atrioventricular junctions revisited

Abstract: There have been suggestions made recently that our understanding of the atrioventricular junctions of the heart is less than adequate, with claims for several new findings concerning the arrangement of the ordinary working myocardium and the specialised pathways for atrioventricular conduction. In reality, these claims are grossly exaggerated. The structure and architecture of the pathways for conduction between the atrial and ventricular myocardium are exactly as described by Tawara nearly 100 years ago. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
99
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 129 publications
(102 citation statements)
references
References 28 publications
2
99
0
1
Order By: Relevance
“…In the human heart, because the distance from the atrium to the crest of the ventricular septum is short, the HB becomes short. 9 The present study showed that the HB recording area is not a small focal point. Although it is possible to record far field HB potentials, we showed that the HB recording area looks like a teardrop or oval shape.…”
Section: Discussionsupporting
confidence: 48%
“…In the human heart, because the distance from the atrium to the crest of the ventricular septum is short, the HB becomes short. 9 The present study showed that the HB recording area is not a small focal point. Although it is possible to record far field HB potentials, we showed that the HB recording area looks like a teardrop or oval shape.…”
Section: Discussionsupporting
confidence: 48%
“…The virtual dissection then serves to confirm the lack of any discrete anatomic entity producing the alleged annulus. 28,41,42 This line is more accurately described as the diameter of the entrance to the arterial roots ( Figure 5, Right panel). The virtual dissection also shows how the semilunar hinges cross the anatomic ventriculo-arterial junction, incorporating crescents of myocardium at the bases of the coronary aortic valvar sinuses (Figure 7).…”
Section: Virtual Dissection Of the Arterial Rootsmentioning
confidence: 99%
“…The free border of this valve continues as the tendon of Todaro and serves as the posterior border of the triangle. The anterior border of the triangle is represented by the septal leaflet of the tricuspid valve, whereas the ostium of the coronary sinus and the septal isthmus (ablation target in reentrant tachycardias) make up the inferior border 11 (Fig. 2).…”
Section: Interatrial Septum Anatomy and Associated Structuresmentioning
confidence: 99%